2010
DOI: 10.1016/j.ajic.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

International Nosocomial Infection Control Consortium (INICC) report, data summary for 2003-2008, issued June 2009

Abstract: Surveillance system [NNIS]) definitions for device-associated health care-associated infection, we collected prospective data from 155,358 patients hospitalized in the consortium's hospital ICUs for an aggregate of 923,624 days. Although device utilization in the developing countries' ICUs was remarkably similar to that reported from US ICUs in the CDC's NHSN, rates of device-associated nosocomial infection were markedly higher in the ICUs of the INICC hospitals: the pooled rate of central venous catheter (CVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
155
13
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 375 publications
(192 citation statements)
references
References 34 publications
11
155
13
13
Order By: Relevance
“…This is the first study presenting DA-HAI rates in ICUs in El Salvador. The PICU CLA-BSI rate was 10.1 (95% CI 7.8 -12.8) per 1,000 central line days in this study, which is higher than the INICC reported rate (7.8 per 1,000 central line days [95% CI 7.1 -8.5]), [6] and higher than the NHSN reported rate of 3.1 (95% CI 2.5 -3.8) [1]. The NICU CLA-BSI rate was 9.9 (95% CI 8.4 -11.6) per 1,000 central line days in this study, which is lower than the INICC reported rate (13.9 per 1,000 central line days [95% CI 12.4 -15.6]) [6] but higher than the NHSN reported rate of 2.9 (95% CI 2.8 -3.0) [1].…”
Section: Microorganism Profilescontrasting
confidence: 80%
See 3 more Smart Citations
“…This is the first study presenting DA-HAI rates in ICUs in El Salvador. The PICU CLA-BSI rate was 10.1 (95% CI 7.8 -12.8) per 1,000 central line days in this study, which is higher than the INICC reported rate (7.8 per 1,000 central line days [95% CI 7.1 -8.5]), [6] and higher than the NHSN reported rate of 3.1 (95% CI 2.5 -3.8) [1]. The NICU CLA-BSI rate was 9.9 (95% CI 8.4 -11.6) per 1,000 central line days in this study, which is lower than the INICC reported rate (13.9 per 1,000 central line days [95% CI 12.4 -15.6]) [6] but higher than the NHSN reported rate of 2.9 (95% CI 2.8 -3.0) [1].…”
Section: Microorganism Profilescontrasting
confidence: 80%
“…Discussion DA-HAIs have been a serious cause of patient attributable mortality in developing countries [6] and have also been a factor of the increase in health care costs [11]. This is the first study presenting DA-HAI rates in ICUs in El Salvador.…”
Section: Microorganism Profilesmentioning
confidence: 91%
See 2 more Smart Citations
“…Eucalyptuses are available in almost all part of the world and in literature Eucalyptus are used as adsorbent or wastewater treatment material. Even for heavy metal ion up to toxic material [29]. In this regard's some alternatively and low cost treatment is try to introduce for treatment of drinking water.…”
Section: Fig 1 Eucalyptus Leaves (E Citriodora)mentioning
confidence: 99%